Investigation of carrier confinement in direct bandgap GeSn/SiGeSn 2D and 0D heterostructures - Denis Rainko (Nature Portfolio, 2018)
Abstract Since the first demonstration of lasing in direct bandgap GeSn semiconductors, the research efforts for the realization of electrically pumped group IV lasers monolithically integrated on Si have significantly intensified. This led to epitaxial studies of GeSn/SiGeSn hetero- and nanostructures, where charge carrier confinement strongly improves the radiative emission properties. Based on recent experimental literature data, in this report we discuss the advantages of GeSn/SiGeSn multi quantum well and quantum dot structures, aiming to propose a roadmap for group IV epitaxy. Calculations based on 8-band k∙p and effective mass method have been performed to determine band discontinuities, the energy difference between Γ- and L-valley conduction band edges, and optical properties such as material gain and optical cross section. The effects of these parameters are systematically analyzed for an experimentally achievable range of Sn (10 to 20 at.%) and Si (1 to 10 at.%) contents, as well as strain values (−1 to 1%). We show that charge carriers can be efficiently confined in the active region of optical devices for experimentally acceptable Sn contents in both multi quantum well and quantum dot configurations.